Spatial Model of COVID 19 Distribution Based on Differences an Climate Characteristics and Environment of According to the Earth Latitude - Oktorie, Olivia; Berd, Isril (Sumatra Journal of Disaster, Geography and Geography Education, 2020)
The purpose of this research is to analyze the spread of COVID-19 on the earth's surface. The method used is a spatial method with the Geographic Information System (GIS) analysis technique. The results of this study explain that the spread of COVID-19 very much occurs in the region of moderate latitude. Besides, tropical climate conditions can also make the virus more quickly become unstable. The Coronavirus spreads faster in countries with high latitudes and humid climates. The spread and concentration of the COVID-19 virus increasingly to the poles are easier to develop, current conditions at high latitudes or poles are not significantly affected due to a small population concentration and population activity, so the virus cannot spread, because the body's virus does not find a host (human) to live and develop.